Multidisciplinary expertise in the diagnosis of cecal lymphoma - Giulia Brooks; Marina Andreetta; Francesco Fascetti Leon; Guendalina Mognato; Calogero Virgone; Monica Zuliani; Alberto Fantin; Marta Pillon; Luisa Santoro; Piergiorgio Gamba; Patrizia Dall'Igna (Elsevier, 2020)
This particular case highlights the importance of a multidisciplinary team expertise in the differential diagnostic process of acute abdominal pain. The case involves a 10-year old Chinese boy who presented with intermittent abdominal pain; the clinical and radiologic picture narrowed the differential diagnosis between an acute appendicitis and an intestinal lymphoma. Diagnosis of a high grade - B lymphoma was made by performing a colonoscopy; this procedure was deemed the best option to obtain a quick diagnosis with low invasiveness.